POST-PANDEMIC LEADERSHIP: TRANSFORMATION TOWARDS MEDICAL RESILIENCE - Indra Kusumah; Efri Widianti; Laila Meiliyandrie Indah Wardani (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2024)
Abstract: The Covid-19 pandemic has brought monumental challenges to the global health sector, exerting immense pressure on healthcare workers and highlighting the need for leadership that prioritizes resilience. Utilizing a scoping review method, this study investigated papers from the EBSCO, SAGE, PubMed, and Scopus databases, focusing on Leadership, Resilience, Healthcare, and Covid-19 as keywords. Sifting through 11 articles that met the established inclusion criteria, the study revealed four important themes: effective leadership styles, factors influencing leadership resilience, difficulties faced by health leaders during the pandemic, and strategies to strengthen leadership resilience. The findings demonstrate that inclusive and innovative leadership is crucial during crisis periods, given the mental and psychological challenges faced by healthcare workers. This study offers a new perspective in the psychological study of leadership during a crisis and emphasizes the importance of strategic revamping in leadership practices to ensure readiness for future outbreaks. The implications of this study are significant, providing a framework for health leaders to adopt a resilience-oriented approach, creating organizations that are more flexible and capable of withstanding pandemic pressures. It also implies the importance of developing policies and leadership training programs that are more focused on resilience in the future. Keywords: Covid-19; Healthcare Workers; Leadership; Resilience; Crisis Management Abstrak: Pandemi Covid-19 telah menimbulkan tantangan monumental pada sektor kesehatan global, mengakibatkan tekanan besar pada tenaga kesehatan dan memperjelas kebutuhan akan kepemimpinan yang mengutamakan resilience. Melalui metode scoping review, penelitian ini menyelidiki makalah dari basis data EBSCO, SAGE, PubMed, dan Scopus dengan fokus pada Leadership, Resilience, Healthcare, dan Covid-19 sebagai kata kunci. Dalam memilah 11 artikel yang memenuhi kriteria inklusi yang telah ditetapkan, studi ini mengungkapkan empat tema penting: gaya kepemimpinan yang efektif, faktor-faktor yang mempengaruhi resilience kepemimpinan, kesulitan yang dihadapi pemimpin kesehatan selama pandemi, dan strategi untuk memperkuat resilience kepemimpinan. Temuan ini memperlihatkan bahwa kepemimpinan yang inklusif dan inovatif adalah sangat krusial dalam periode krisis, mengingat tantangan mental dan psikologis yang dihadapi oleh pekerja kesehatan. Studi ini menawarkan perspektif baru dalam kajian psikologi kepemimpinan di masa krisis dan menekankan pentingnya pembenahan strategis dalam praktek kepemimpinan untuk memastikan kesiapsiagaan dalam menghadapi wabah yang akan datang. Implikasi dari studi ini sangat penting, memberikan kerangka kerja bagi pemimpin kesehatan untuk mengadopsi pendekatan yang berorientasi pada ketahanan, menciptakan organisasi yang lebih fleksibel dan mampu mengatasi tekanan pandemi. Hal ini juga menyiratkan pentingnya pengembangan kebijakan dan program pelatihan kepemimpinan yang lebih fokus pada resilience di masa mendatang. Kata kunci: Covid-19; Kepemimpinan; Petugas Kesehatan; Resiliensi; Manajemen Krisis